Changes in birth-related pain perception impact of neurobiological and psycho-social factors - Berlit, Sebastian; Lis, Stefanie; Häfner, Katharina Aline; Kleindienst, Nikolaus; Baumgärtner, Ulf; Treede, Rolf-Detlef; Sütterlin, Marc; Schmahl, Christian (Archives of gynecology and obstetrics, 2017)
PurposeTo analyse post-partum short- and long-term pain sensitivity and the influence of endogenous pain inhibition as well as distinct psycho-social factors on birth-related pain.MethodsPain sensitivity was assessed in 91 primiparous women at three times: 2-6 weeks before, one to 3 days as well as ten to 14 weeks after childbirth. Application of a pressure algometer in combination with a cold pressor test was utilised for measurement of pain sensitivity and assessment of conditioned pain modulation (CPM). Selected psycho-social factors (anxiety, social support, history of abuse, chronic pain and fear of childbirth) were evaluated with standardised questionnaires and their effect on pain processing then analysed.ResultsPressure pain threshold, cold pain threshold and cold pain tolerance increased significantly directly after birth (all p < 0.001). While cold pain parameters partly recovered on follow-up, pressure pain threshold remained increased above baseline (p < 0.001). These pain-modulating effects were not found for women with history of abuse. While CPM was not affected by birth, its extent correlated significantly (r = 0.367) with the drop in pain sensitivity following birth. Moreover, high trait anxiety predicted an attenuated reduction in pain sensitivity (r = 0.357), while there was no correlation with fear of childbirth, chronic pain and social support.ConclusionPain sensitivity showed a decrease when comparing post-partum with prepartum values. The extent and direction of CPM appear to be a trait variable that predicted post-partum hypalgesia without being changed itself. Post-partum hypalgesia was reduced in women with a history of abuse and high trait anxiety, which suggests that individual differences in CPM affect childbirth experience.